2020
DOI: 10.3390/plants9091150
|View full text |Cite
|
Sign up to set email alerts
|

Applied Barcoding: The Practicalities of DNA Testing for Herbals

Abstract: DNA barcoding is a widely accepted technique for the identification of plant materials, and its application to the authentication of commercial medicinal plants has attracted significant attention. The incorporation of DNA-based technologies into the quality testing protocols of international pharmacopoeias represents a step-change in status, requiring the establishment of standardized, reliable and reproducible methods. The process by which this can be achieved for any herbal medicine is described, using Hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 103 publications
1
23
0
Order By: Relevance
“…Herbal products are sold as ground or powdered form of a raw herb, which makes correct botanical identification difficult [ 22 ]. DNA barcoding constitutes a very useful tool for quality control and, consequently, for clinical safety [ 23 , 24 ]. Molecular analyses is crucial for accurate and fast identification of medicinal plants, since the plant fragments sold in the market is difficult to identify using traditional methods especially due to lack of morphological features.…”
Section: Resultsmentioning
confidence: 99%
“…Herbal products are sold as ground or powdered form of a raw herb, which makes correct botanical identification difficult [ 22 ]. DNA barcoding constitutes a very useful tool for quality control and, consequently, for clinical safety [ 23 , 24 ]. Molecular analyses is crucial for accurate and fast identification of medicinal plants, since the plant fragments sold in the market is difficult to identify using traditional methods especially due to lack of morphological features.…”
Section: Resultsmentioning
confidence: 99%
“…Although rbcL is widely used because of its easy amplification and high sequence quality, the region shows low intraspecific variation due to its slow evolutionary rate; thus it can be useful as a barcode only above genus level or in combination with other loci [15,16]. Howard et al [33] reported that despite being able to discriminate Hypericum species at the genus and section level, rbcL cannot differentiate the closely related species H. perforatum and H. maculatum. Our silico analysis results show that this region cannot be used effectively for the discrimination of Hypericum species, so we examined only matK and trnH-psbA for the identification of Hypericum species from NE Greece.…”
Section: Discussionmentioning
confidence: 99%
“…matK region is often difficult to amplify and sequence because of its relatively large size (about 1000 bp) and the lack of universal primers [36]. In Hypericum species, poor PCR amplification of matK has been reported by Howard et al [33] using published primers. Likewise, in our study, the 2 pairs of primers that have been previously used for the amplification of Hypericum species [37] failed to amplify the matK region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations